The role of theory in mitigating the ‘reproducibility crisis’ - Luis Marone (Ecología Austral, 2024)
The lack of reproducibility of scientific results is jeopardizing the trust in science. An effort to inform the dynamic, but non-arbitrary, nature of scientific evidence is required along with strengthening the reliability of published results. Concerns and actions aimed at testing and increasing the reproducibility of scientific conclusions are usually directed at increasing data validation through careful management of the data-curation process, paying attention to the empirical aspects of hypotheses testing. But important as they are, these aspects may be vulnerable to the perils of radical empiricism and therefore should be combined with more theoretical and conceptual tools. Pattern consistency and an understanding of the physiological, behavioral, or ecological mechanisms that cause patterns make scientific assertions more robust. Testing a priori hypotheses (e.g., about functional biological traits) with fresh (and redundant) evidence offers theoretical as well as empirical support for ecological research and may help strengthen the reliability of published results.